Sikap Nelayan terhadap Pemberlakuan Peraturan Menteri Nomor 2 Tahun 2015 Tentang Pelarangan Alat Tangkap Ikan (Studi Deskriptif di Desa Warulor Kecamatan Paciran Kabupaten Lamongan) - Rahayu, Fitria; A, Arif (University of Jember, 2017)
Abstract The sea is the largest sector in meeting the needs of fishermen. However, as the increasingly modernization of fishing technology has provided many benefits, one of them is increasing fishery production. overfishing. Directly raises intense competition in the seizure of fishery resources. This makes it more difficult for fishermen to meet their needs. This research uses qualitative approach, descriptive type, with research location in Warulor village of Paciran Subdistrict of Lamongan Regency. Determination of Informants with Purposive technique. Data collection uses observation, interviews, and documentation. Data analysis using Miles and Huberman model. Test data validity using triangulation of data source. The results of this study is the attitude of fishermen to the ministerial regulation number 2 of 2015 on the ban on the use of fishing gear. Since the enactment of ministerial regulations, various forms of fishermen attitude have emerged. Sometimes the regulatory fishermen are caused by various factors such as: (1) Small fish caught and dead wasted, (2) Obeying the rules made by the state, (3) The fishing catch is less than the maximum, (4) The destruction of the environment habitat Marine waters. The fishermen who do not obey the rules are caused by various factors such as: (1) Fish catch every day and do not know the weather, (2) trustworthy factor believed, (3) fishing gear effective and profitable fisherman, (4) personal experience, (5) Substitute guarantees of fishing gear as a solution, not yet favoring fishermen, (6) irrelevant rules, (7) fisherman attitude indifferent, (8) already used by fishermen for generations. Fishermen who use fishing equipment that belong to the category of species (seine nets) can damage marine ecosystems and often trigger conflicts between fishermen. The impact of the use of unsustainable fishing gear is the threat of marine habitat, the condition of bad coral reefs, the loss of catch of fish species, and the decline in fisherman's income.